Green Transportation: A Foresight Study of Electric Vehicles Adoption in Malaysia - Pua Hong Jie; Wan Nurul Karimah Wan Ahmad (Research in Management of Technology and Business, 2024)
Electric vehicle is one of the most important innovations that have revolutionized the industry especially in automotive industry and nowadays, electric vehicles have become popular worldwide. The purpose of this research is to identify the key drivers for the electric vehicles adoption in Malaysia and study the future scenario of electric vehicles in Malaysia. The study uses STEEPV analysis to identify issues, challenges, and trends of electric vehicles based on social, technological, environmental, economic, political, and value aspects. The research had been conducted among Malaysian consumers; the research had collected 251 responses from respondent with a response rate of 65.36%. Impact-uncertainty analysis can help to determine future scenario based on the highest impact-uncertainty level to study the future scenario. For this study, top drivers are availability of charging infrastructure and purchasing and maintenance cost of electric vehicle and scenarios derived from these top drivers are high availability of charging infrastructure, low availability of charging infrastructure, high purchasing and maintenance cost of electric vehicle and low purchasing and maintenance cost of electric vehicle. This scenario can help dealers, government, and all Malaysian have a better understanding about electric vehicle. The best scenario for study is mature adoption for adopting electric vehicle in Malaysia to develop the better world for future and the worst scenario is absence of electric vehicle so that the future stakeholders should be avoided this scenario happened in Malaysia after 10 years.